Cymbidium lancifolium Hook. (Orchidaceae): New Discovery from the Western Himalaya - Singh, Manoj; Singh, S. K.; Joshi, Jyoti Prakash; Negi, Harish; Joshi, Rajendra Prasad (Indian Forester, 2023)
No Abstract.